Cytotoxicity of Different Nano Composite Resins on Human Gingival and Periodontal Ligament Fibroblast Cell Lines: An In Vitro Study - Kavuncu, Gamze (Biomedicines, 2020)
The aim of this study is to determine the cytotoxicity of three different nano composite resins (CRs) on human gingival fibroblast (hGF) and periodontal ligament fibroblast (hPDLF) cell lines. These CRs selected were nanohybrid organic monomer-based Admira Fusion (AF), nanohybrid Bis-(acryloyloxymethyl) tricyclo [5.2.1.0.sup.2,6] decane-based Charisma Topaz (CT), and supra nano filled resin-based Estelite Quick Sigma (EQS). MTT assay was performed to assess the cytotoxicity of CRs at 24 h and one week. AF and EQS applied on hGF cells at 24 h and one week demonstrated similar cytotoxic outcomes. Cytotoxicity of CT on hGF cells at one week was higher than 24 h (p = 0.04). Cytotoxicity of CT on hGF cells was higher at 24 h (p = 0.002) and one week (p = 0.009) compared to control. All composites showed higher cytotoxicity on hPDLF cells at one week than the 24 h (AF; p = 0.02, CT; p = 0.02, EQS; p = 0.04). AF and EQS demonstrated lower cytotoxicity on hPDLF cells than the control group at 24 h (AF; p = 0.01, EQS; p = 0.001). CT was found more cytotoxic on hPDLF cells than the control (p = 0.01) and EQS group (p = 0.008) at one week. The cytotoxicity of CRs on hGF and hPDLF cells vary, according to the type of composites, cell types, and exposure time.